Modern Tragic Characters in The Banshees of Inisherin - Elif Taşdemir Şanlı (Filmvisio)
While tragic art creates the opportunity to reveal the contradictions and conflicts of the period in which it emerged in both social and individual contexts, it can also reveal a universal human condition. Just as wars, deaths, and natural and man-made disasters can be described as ‘tragic,’ individual situations such as separations, despair, and anxiety can also be tragic. The originally applied form of tragedies, which we know to have emerged in Ancient Greece in the fifth century BC, has changed over the centuries, as have the changing culture, society, and forms of government. In Ancient Greek tragedies, which generally take their subject from myths, the place of the noble hero who incurred the wrath of the gods, exceeded the boundaries beyond measure, and committed a tragic crime has been replaced by ordinary people who experience tragic situations, sometimes due to external reasons arising from the existing order, and sometimes due to the end of a friendship, in modern tragedies. This paper aims to discuss in which situations tragic patterns appear in Irish director and screenwriter Martin McDonagh’s The Banshees of Inisherin (2022) in the context of modern tragedy theory. The tragic situations of the characters Padraic Suilleabhain, Colm Doherty, and Dominic Kearney in the film were determined, and their inability to escape their current situation was examined using the interpretive content analysis method.This deadlock has created tragic patterns such as the pessimism and hopelessness that the war affects the people living on an island while the war continues, leading to separation, violence, and death.